Influence of elevated temperature on release of bound chlorides from chloride-admixed plain and blended cement pastes. (1st February 2016) - Xu, Jinxia; Song, Yingbin; Jiang, Linhua; Feng, Wei; Cao, Yalong; Ji, Weiwei
Highlights: We examine the release of bound chloride due to the elevated temperature. The amount of released chloride ions is affected by W/B ratio, total chloride, etc. We discuss influences of SF and GGBS on corrosion risk at different temperatures. Abstract: This paper is aimed to evaluate the influence of elevated temperature on the release of bound chloride ions from pastes made of ordinary Portland cement alone and a mixture of ordinary Portland cement and the partial replacements of cement with 10% silica fume (SF) and 50% ground granulated blast furnace slag (GGBS). Three ratios of water to binder (W/B) and four levels of total chloride ions were applied. The contents of free chloride ions and pH values in the pastes at different temperatures (0 °C, 20 °C, 40 °C and 60 °C) were determined by the measurements in the suspensions with 1:10 mass ratio of triturated paste powders to water. The results indicate that the increase of temperature can release partially the bound chloride ions. The amount of released chloride ion is dependent on the W/B ratio, content of total chloride ions and temperature range. Besides, the released chloride ions for the partial replacements of cement with 10% SF and 50% GGBS exhibits different trends with the temperature range. Furthermore, the influences of 10% SF and 50% GGBS on the corrosion risk of reinforcing steel at different temperatures are discussed by means of the index of Cl − /OH − .